A Literature Review and Conceptual Framework on Corporate Strategic Foresight – What Value Created as a Source of Competitive Advantage in the Automotive Industry - Jaka Purwanto; Reza Ashari Nasution; Yudo Anggoro (Jurnal Manajemen Indonesia, 2023)
Nowadays, the challenge in the automotive industry is more demanding due to the increase in dynamicity and complexity of environmental changes in the external business environment. Under the increasing uncertainty level, companies require a strategic approach to face these challenges. One of the essential techniques used to meet the environmental dynamic is corporate strategic foresight. Hence, it is essential to understand its value creation because the business environment is getting more uncertain and intense competition. However, the investigation of corporate strategic foresight value creation in the automotive industry is limited. This study aims to investigate corporate strategic foresight value creation and attempts to answer the research question of what value is created from corporate strategic foresight as a source of the firm's future competitive advantage in the automotive industry. This study employed a narrative literature review method based on the existing literature as a part of the qualitative study. The result showed a novelty in the conceptual framework of corporate foresight value creation in the automotive industry. It also provides insight into how organizational values are created to enhance the capability to gain competitive advantage, which contributes to practical especially to managerial and practitioners’ automotive industry for a better understanding of corporate strategic foresight. Keywords— automotive; competitive advantage; corporate strategic foresigh; environmental dynamic; value creation